STUDI KEPUSTAKAAN PERLINDUNGAN HAK PENDIDIKAN KORBAN EKSPLOITASI PEKERJA ANAK - Faiza Mutia Razan; Taopik Rahman; Purwati (Jurnal Genta Mulia, 2024)
The protection of children's right to education is a crucial aspect of nation-building. However,children who become victims of child labor exploitation are vulnerable to violations of this right. Thisstudy aims to identify the issues surrounding the educational rights of children who are victims ofchild labor exploitation and formulate necessary policy recommendations. The research aims to highlight the low level of education, barriers to accessing education, and the negative impactsexperienced by children who are victims of child labor exploitation. Additionally, its objectivesinclude formulating policy recommendations to enhance the protection of children's educationalrights. The method employed in this study is literature review. Data collection involves a review ofbooks, literature, records, and reports related to the educational rights issues of children who arevictims of child labor exploitation. The study identifies the low level of education received, barriersto accessing education, and negative impacts such as decreased academic achievement as the mainissues faced by children who are victims of child labor exploitation. The policy recommendationsemphasize the importance of law enforcement, improved access to education, integration of formaland non-formal education, and government commitment to poverty alleviation. Efforts to raisepublic awareness are also a focus in formulating policy recommendations.